Analisis Retorika Aritoteles pada Pidato Presiden Prabowo Subianto Terlalu Lama Rakyat Jadi Penonton Kekayaaan - Renita Asriani; Rhani Febria (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the use of Aristotle’s rhetorical strategies, namely ethos, pathos, and logos, in President Prabowo Subianto’s speech entitled “For Too Long, the People Have Only Been Spectators of Their Own Wealth” delivered during the commemoration of Pancasila Day on June 1, 2026. The study employed a qualitative method with a rhetorical analysis approach. The research data consisted of the speech transcript obtained from the speech video published on YouTube. Data were collected through documentation, observation, note-taking, and classification based on the categories of ethos, pathos, and logos. The data were analyzed descriptively by identifying and interpreting rhetorical elements contained in the speech. The findings reveal that the speech incorporates all three Aristotelian rhetorical appeals. Ethos is reflected in Prabowo’s emphasis on his role and responsibility as the President of the Republic of Indonesia and his references to the national figure Sukarno to strengthen the credibility of his message. Pathos is demonstrated through efforts to evoke audience emotions by portraying economic inequality, the condition of people who have not fully benefited from the nation’s natural resources, and concerns for vulnerable social groups. Logos is evident in the rational arguments regarding economic disparities, the use of Article 33 of the 1945 Constitution as a constitutional foundation, and the presentation of government programs as solutions to national economic challenges. The study concludes that the combination of ethos, pathos, and logos is effectively utilized to gain public support for the concept of Pancasila Economy and the national development agenda proposed by President Prabowo Subianto.